Potensi pemanfaatan limbah sistem integrasi tanaman-ternak di Pesantren Tradisional pedesaan (The use-potential of plant-animal system wastes on Traditional Islamic boarding school at rural area) - Hardoyo, Hardoyo; Kusarpoko, Budi; Tri Atmodjo, Mochamad Chaerudin; Yusmiati, Yusmiati; Putranto, Andi Marjono (Universitas Negeri Yogyakarta, 2023)
Integrated/combined farming is a good way to optimize the use of resources and maximize income. Ruminant livestock is a type of other livestock types that plays an important role in sustainable agricultural systems because this type of livestock produces fertilizers and can utilize agricultural waste as fodder. Manure can be an alternative energy source for livestock farmers. An anaerobic digester will partially convert manure to energy in the form of biogas which contains methane. The main product of cassava crops is cassava. In this research, a toxic cassava which usually plant around pesantren. That could be used as food material. The cassava leaf could used as a source of silage production, and the silage quality is good until 60 days of storage. This silage was prepared for the drying season which at that time was difficult to find fresh feed. The cow dung is used as green manure fertilizer for cassava plants. The cow dung was fermented by an anaerobic bioreactor to achieve biogas and slurry. The biogas with methane as the main component is bioenergy that can used as a mantel lamp (Petromax) for lightening and a gas stove for cooking in Pesantren. The Slurry can able used as fertilizer and the eel cultivation.